Variation in Physician Charges and Medicare Payments for Hand Surgery - Menendez, Mariano E.; Parrish, Raymond C., II; Ring, David; Chen, Neal C. (Journal of Hand and Microsurgery, 2019)
Purpose To assess national and state-level variation in physician charges (full amounts requested before payments are negotiated) and Medicare payments for common hand procedures.Materials and Methods Using the Medicare Provider Utilization and Payment Data Public Use File for 2012, we evaluated national and state variations in physician charges and Medicare payments for carpal tunnel release, trigger finger release, trigger finger injection, closed treatment of distal radius fracture, and interposition arthroplasty, intercarpal or carpometacarpal joints. We assessed variation, using the coefficient of variation. We also determined the correlation between charges and payments, as well as the association of patient volume with charges and payments.Results There was wide state-level variation in physician charges for carpal tunnel release (11-fold), trigger finger release (9.6-fold), and trigger finger injection (5.5-fold). On a national level, physician charges varied substantially for carpal tunnel release, trigger finger release, trigger finger injection, closed treatment of distal radius fracture, and interposition arthroplasty, intercarpal or carpometacarpal joints. Medicare payments varied to a lesser extent. The correlations between physician charges and Medicare reimbursements were not strong. Weak to no correlations were noted between patient volume and both charges and payments.Conclusion Physician charges for hand surgery vary substantially across states and nationally, and they do not correlate well with Medicare payments and surgeon volume. As the health care market transitions toward more restrictive physician networks and high-deductible plans, protecting uninsured and out-of-network patients from unexpected, high medical bills should be a policy priority.Type of Study/Level of Evidence Economic/Decision Analysis, Level III study.
Keywords: hand surgery; Medicare payments; physician charges; reimbursement